Some lumbar sympathetic neurons develop a glutamatergic phenotype after peripheral axotomy with a note on VGLUT2-positive perineuronal baskets - Brumovsky, Pablo Rodolfo (2011)
Glutamate is the main excitatory neurotransmitter in the nervous system, including in primary afferent neurons. However, to date a glutamatergic phenotype of autonomic neurons has not been described. Therefore, we explored the expression of vesicular glutamate transporter (VGLUT) types 1, 2 and 3 in lumbar sympathetic chain (LSC) and major pelvic ganglion (MPG) of naïve BALB/C mice, as well as after pelvic nerve axotomy (PNA), using immunohistochemistry and in situ hybridization. Colocalization with activating transcription factor-3 (ATF-3), tyrosine hydroxylase (TH), vesicular acetylcholine transporter (VAChT) and calcitonin gene-related peptide was also examined. Sham-PNA, sciatic nerve axotomy (SNA) or naïve mice were included. In naïve mice, VGLUT2-like immunoreactivity (LI) was only detected in fibers and varicosities in LSC and MPG; no ATF-3-immunoreactive (IR) neurons were visible. In contrast, PNA induced upregulation of VGLUT2 protein and transcript, as well as of ATF-3-LI in subpopulations of LSC neurons. Interestingly, VGLUT2-IR LSC neurons coexpressed ATF-3, and often lacked the noradrenergic marker TH. SNA only increased VGLUT2 protein and transcript in scattered LSC neurons. Neither PNA nor SNA upregulated VGLUT2 in MPG neurons. We also found perineuronal baskets immunoreactive either for VGLUT2 or the acetylcholinergic marker VAChT in non-PNA MPGs, usually around TH-IR neurons. VGLUT1-LI was restricted to some varicosities in MPGs, was absent in LSCs, and remained largely unaffected by PNA or SNA. This was confirmed by the lack of expression of VGLUT1 or VGLUT3 mRNAs in LSCs, even after PNA or SNA. Taken together, axotomy of visceral and non-visceral nerves results in a glutamatergic phenotype of some LSC neurons. In addition, we show previously non-described MPG perineuronal glutamatergic baskets.